Fluorescently tagged nanobodies and NanoBRET to study ligand-binding and agonist-induced conformational changes of full-length EGFR expressed in living cells - Comez, Dehan; Glenn, Jacqueline; Anbuhl, Stephanie M.; Heukers, Raimond; Smit, Martine J.; Hill, Stephen J.; Kilpatrick, Laura E. (Frontiers in Immunology, 2022)
Introduction The Epidermal Growth Factor Receptor is a member of the Erb receptor tyrosine kinase family. It binds several ligands including EGF, betacellulin (BTC) and TGF-α, controls cellular proliferation and invasion and is overexpressed in various cancer types. Nanobodies (VHHs) are the antigen binding fragments of heavy chain only camelid antibodies. In this paper we used NanoBRET to compare the binding characteristics of fluorescent EGF or two distinct fluorescently labelled EGFR directed nanobodies (Q44c and Q86c) to full length EGFR. Methods Living HEK293T cells were stably transfected with N terminal NLuc tagged EGFR. NanoBRET saturation, displacement or kinetics experiments were then performed using fluorescently labelled EGF ligands (EGF-AF488 or EGF-AF647) or fluorescently labelled EGFR targeting nanobodies (Q44c-HL488 and Q86c-HL488). Results These data revealed that the EGFR nanobody Q44c was able to inhibit EGF binding to full length EGFR, while Q86c was able to recognise agonist bound EGFR and act as a conformational sensor. The specific binding of fluorescent Q44c-HL488 and EGF-AF488 was inhibited by a range of EGFR ligands (EGF> BTC>TGF-α). Discussion EGFR targeting nanobodies are powerful tools for studying the role of the EGFR in health and disease and allow real time quantification of ligand binding and distinct ligand induced conformational changes.